Is Physical Activity a Good Way to Improve Quality of Life in the Elder Population? - Bento, Teresa; Vitorino, Anabela; Cid, Luís (Journal of Tourism, Sustainability and Well-being, 2014)
Background: Although evidence demonstrates that physical activity beneficially influences major chronic illnesses, older adults remain sedentary. Many interventions to increase physical activity intend to reduce disease complications as well as improve quality of life by enhancing physical function in our even more aging society. Objectives: The purpose of this study was to summarize knowledge on randomized controlled trials studying the effects of physical activity interventions on quality of life in the elder population. Methods: Randomized controlled trials, systematic reviews or meta-analysis were searched in the Pubmed data base. Search terms: “quality of life”, “intervention” and “physical activity” were used to identify English written articles, with humans older than 65 years. Results: From the initial screening of 234 titles, only 5 articles met the inclusion criteria and were included in the final analysis. Conclusions: Physical activity interventions seem to have a slight effect on physical function and in improving quality of life of people aged 65 and over. More intervention studies involving physical activity in older people should include measures of quality of life as primary outcome, as well as a standardization of measures would help to compare results and enlarge the evidence base in this area.